Development of a Youth Civic Engagement Program: Process and Pilot Testing with a Youth‐Partnered Research Team. Issue 1 (4th August 2021) - Alegría, Margarita; Alvarez, Kiara; NeMoyer, Amanda; Zhen‐Duan, Jenny; Marsico, Christine; O'Malley, Isabel Shaheen; Mukthineni, Ravali; Porteny, Thalia; Herrera, Carolina‐Nicole; Najarro Cermeño, Jesse; Kingston, Kyle; Sisay, Emnet; et al.
Abstract: Although research suggests neighborhood‐level factors influence youth well‐being, few studies include youth when creating interventions to address these factors. We describe our three‐step process of collaborating with youth in low‐income communities to develop an intervention focused on civic engagement as a means to address neighborhood‐level problems impacting their well‐being. In the first step, we analyzed qualitative interviews from a project in which youth shared perceptions about their neighborhoods (e.g., interpersonal relations with neighbors and institutions). Three major themes were identified: pride in youth's communities, desire for change, and perceptions of power and responsibility. Based on these themes, we completed the second step: developing a civic engagement and leadership program, called LEAP, aimed at helping youth take an active role in addressing neighborhood problems. In the third step, we collaborated with youth who completed a pilot version of the civic program and provided feedback to finalize it for large‐scale testing. While discussing our process, we highlight the importance of including youth voices when developing programs that affect them. Furthermore, we note the need for more research exploring whether civic engagement serves as a mechanism for encouraging youth involvement in addressing neighborhood‐level health disparities and identifying potential psychological costs of such involvement. Highlights: Youth should have a voice in the creation and implementation of programs intended for them. Neighborhoods may impact youth wellbeing through resource availability and a negative social mirror. Developing programs through academic‐youth partnerships can facilitate aligning with youth's goals. Youth can identify and problem‐solve their neighborhood challenges as civic leaders.